Laser Welding - Na, Xiaodong; Na, Xiaodong (IntechOpen, 2010)
This book is entitled to laser welding processes. The objective is to introduce relatively established methodologies and techniques which have been studied, developed and applied either in industries or researches. State-of-the art developments aimed at improving or next generation technologies will be presented covering topics such as monitoring, modelling, control, and industrial application. This book is to provide effective solutions to various applications for field engineers and researchers who are interested in laser material processing.
English
Keywords: Other technologies & applied sciences; Applied optics